MINIATUR PENGAMAN TOWER TERHADAP PENCURI BERBASIS MIKROKONTROLER ATMEGA8 MENGGUNAKAN SENSOR PIR (PASSIVE INFRA RED) DAN LIMIT SWITCH DENGAN SISTEM SCADA - Utami, Dyah Palupi; Subali, Subali (Gema Teknologi, 2014)
Dyah Palupi Utami, Subali, in this paper explain that information security is a very important thing, therefore we need a system that can identify the users who will be accessing an information system security. SCADA stands for Supervisory Control And Data Acquisition meaningful data acquisition and supervisory control according to the indication. SCADA is not a complete control system, but more focused on the level of supervision. Thus, SCADA is a software package that is positioned to hardware connected to the system, generally through a microcontroller. PIR sensors and touch sensors. Where the sensor will detect the presence of human presence and sends a signal to the microcontroller. Indicator lights and an alarm will sound. The microcontroller will send a signal to the PC. In this study, applied in the security tower using a computer to pengkontrolan system as well as a display monitor and a monitoring system security information on this tool. Safety and time efficiency into consideration in making this tool, where the use of an identification system is needed. This research is focused on developing the design and simulation of SCADA systems used in information security. Keywords: tower, microcontroller, PIR sensors, SCADA